Marketing library services online: Strategies and challenges for academic libraries - Agha, Syed Salim (2004)
The dynamism of the higher education scene in Malaysia continues to have a catalytic effect on the Institutions of Higher Education, both public and private. The competition between and among these institutions is immense. There is an inevitable push by most institutions to reform, to improve and to set and establish higher standards in all fields of endeavor. The demand for quality services from the public, university students, academic staff and management is driving academic institutions to change and change for the better. This same demand is being felt by academic libraries for increased, relevant, useful and sophisticated library services.